2011
DOI: 10.1080/00224499.2010.535623
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Partners, Friends, Friends with Benefits, and Casual Acquaintances as Sexual Partners

Abstract: The purpose of the present study was to provide a detailed examination of sexual behavior with different types of partners. A sample of 163 young adults reported on their light nongenital, heavy nongenital, and genital sexual activity with romantic partners, friends, and casual acquaintances. They described their sexual activity with “friends with benefits” as well as with friends in general. Young adults were most likely to engage in sexual behavior with romantic partners, but sexual behavior also often occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 19 publications
3
48
0
6
Order By: Relevance
“…The borders between same-sex groups begin to dissolve in middle school, but othersex friendships are still highly atypical and pressure to conform to same-sex structures remains considerable. Sexual feelings and jealousy may arise creating conflict (Furman & Shaffer, 2011). It is also likely that some portion of mixed-sex friendship briefly passed through a romantic phase prior to relationship dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…The borders between same-sex groups begin to dissolve in middle school, but othersex friendships are still highly atypical and pressure to conform to same-sex structures remains considerable. Sexual feelings and jealousy may arise creating conflict (Furman & Shaffer, 2011). It is also likely that some portion of mixed-sex friendship briefly passed through a romantic phase prior to relationship dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested that true friends was the most frequent type of FWB relationship individuals reported having, but it only represented one fourth of the total FWB relationships reported. Because FWB relationships can differ with regard to who participates, some researchers allow individuals to use their own definition of FWB relationships (Furman & Shaffer, 2011).…”
Section: Friends With Benefits (Fwb) Relationshipsmentioning
confidence: 99%
“…The little psychological research that has been conducted on casual or non-romantic sex is predominantly quantitative, focused on individual attitudes and personality characteristics and generally based on the assumption that such sexual activities are self-evidently problematic (Furman & Shaffer, 2011;Mikach & Bailey, 1999;Wentland, Herold, Desmarais, & Milhausen, 2009). Further, it has generally not considered the gender dynamics of nonromantic sex encounters, nor the gendered power relations between men and women and the discourses in which they, and sexual encounters, are situated.…”
Section: Introductionmentioning
confidence: 99%